The Risk Perception For Consumer Segments In E-CommerceAnd Its Implication For The Marketing Strategy - Corina Pelău; Irina Bena (Amfiteatru Economic Journal, 2010)
During the past years, the Internet has gained a very important role in our everyday lives as well as in the business environment. This online trend developed also in the way companies interact with their customers by means of Internet platforms, or in the form of e-commerce. Despite the easiness with which customers order products from home, the online shopping has also many risks. Most of the risks are related to the lack of information about the company who sells online or the uncertainty that the ordered products will be delivered. Starting with the presentation of the processes taking place in online shopping, the present article reviews the rights consumers have when buying online and then focuses on researching the risk of online shopping as perceived by Romanian consumers. The study analyzes the differences in the risk perception and the willingness to buy online in the future depending on gender, age or income. The way in which consumers perceive risks affects the company's marketing strategy, because if consumers see a greater risk in online transactions, the probability that they will buy online decreases. Consequently the company must focus its communication strategy on the reduction of the risk perception.
Keywords: M39; 330; consumer behaviour; risk perception; e-commerce; consumer rights; online marketing